Why don't all species overexploit? - Vuorinen Katariina E M; Oksanen Tarja; Oksanen Lauri; Vuorisalo Timo; Speed James D M (WILEY, 2022)
Overexploitation of natural resources is often viewed as a problem characteristic of only the human species. However, any species could evolve a capacity to overexploit its essential resources through natural selection and competition, even to the point of resource collapse. Here, we describe the processes that potentially lead to overexploitation and synthesize what is known about overexploitation limiters in other species. We propose that there are five pathways that counteract the evolutionary drive towards overexploitation and/or mitigate its consequences: top-down trophic control, interference, cost-efficiency tradeoffs, resource trait evolution, and spatial heterogeneity. These mechanisms constrain the number of exploiters and/or lower the rate of the resource usage at the individual level. We hypothesize that in ecosystems with reasonable functional diversity, coevolution strengthens this limiter network, preventing overexploitation, and thus argue that diversity begets stability via evolution. Violent population cycles in species-poor northern ecosystems and eruptions of invading alien species are exceptions that confirm this rule, because these ecosystems either lack functional diversity or there has not been enough time for coevolution to play out its stabilizing role. We propose that the overexploitation by our own species could be prevented via a network of socio-economical limiters that act in an analogous way.